Comparison of Incline Plyometric with Plane Plyometric Training on Dynamic Balance and Vertical Jump Performance in Volleyball Athletes: A Randomized Controlled Study - Saurabh Sharma (Current Innovations in Medicine and Medical Science Vol. 6, 2022)
The aim of the study was to analyze and compare the effect of inclined and plane plyometrics training on dynamic balance and jumping performance in collegiate volleyball players. The study adopted a randomized controlled trial design.A total of forty volleyball athletes were selected for the study from the university team. They were randomly divided into two group i.e. Inclined plyometric (IP) and plane plyometrics (PP) and athletes underwent 6 weeks of plyometric training and they were assessed for dynamic balance and jumping performance. The result of the study suggests that incline plyometric training significantly improved the jumping performance while the dynamic balance exhibited similar improvement in both the groups. It is recommended that incline plyometric can be used during training of volleyball athletes to enhance jumping performance.